Altered Expression of Circadian Clock Genes in Patients with Atrial Fibrillation Is Associated with Atrial High-Rate Episodes and Left Atrial Remodeling - Yung-Lung Chen; Jiin-Haur Chuang; Hui-Ting Wang; Huang-Chung Chen; Wen-Hao Liu; Ming-Yu Yang (Diagnostics, 2021)
A prominent circadian variation is present in atrial fibrillation (AF) attacks that may be related to the expression of circadian clock genes. Little is known about the expression of circadian clock genes in AF. We prospectively enrolled 73 patients who had received pacemaker implantation, in order to define the burden of atrial high-rate episodes (AHREs) accurately. AF was diagnosed clinically in 43 (59%) patients (15 with persistent AF and 28 with paroxysmal AF). The expression levels of circadian clock genes of peripheral blood leukocytes were checked. There were more males and patients with a larger left atrial (LA) size and lower expression levels of BMAL1, CRY2, NR1D1, NR1D2, PER2, RORA, RORC, and TIM genes in persistent AF group than in other groups. There was a significant correlation between higher AHRE burden and larger LA size and between higher AHRE burden and decreased expression of circadian clock genes in patients with AF. LA volume and the expression of CRY1, NR1D1, and RORA are significantly associated with AHRE burden. However, the underlying mechanism needs to be elucidated in further studies.